The Efficacy and Safety of Bivalirudin Versus Heparin in the Anticoagulation Therapy of Extracorporeal Membrane Oxygenation: A Systematic Review and Meta-Analysis - Ma, Min; Liang, Shichu; Zhu, Jingbo; Dai, Manyu; Jia, Zhuoran; Huang, He; He, Yong (Frontiers in Pharmacology, 2022)
Background: Bivalirudin is a direct thrombin inhibitor (DTI) that can be an alternative to unfractionated heparin (UFH). The efficacy and safety of bivalirudin in anticoagulation therapy in extracorporeal membrane oxygenation (ECMO) remain unknown. Methods: This study followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. A systematic literature search was performed in PubMed, EMBASE, and The Cochrane Library databases to identify all relevant original studies estimating bivalirudin’s efficacy and safety versus UFH as anticoagulation therapy in ECMO. The time limit for searching is from the search beginning to June 2021. Two researchers independently screened the literature, extracted data and evaluated the risk of bias of the included studies. The meta-analysis (CRD42020214713) was performed via the RevMan version 5.3.5 Software and STATA version 15.1 Software. Results: Ten articles with 847 patients were included for the quantitative analysis. Bivalirudin can significantly reduce the incidence of major bleeding in children (I2 = 48%, p = 0.01, odd ratio (OR) = 0.17, 95% confidence interval (CI): 0.04–0.66), patient thrombosis (I2 = 0%, p = 0.02, OR = 0.58, 95% CI: 0.37–0.93), in-circuit thrombosis/interventions (I2 = 0%, p = 0.0005, OR = 0.40, 95% CI: 0.24–0.68), and in-hospital mortality (I2 = 0%, p = 0.007, OR = 0.64, 95% CI: 0.46–0.88). Also, comparable clinical outcomes were observed in the incidence of major bleeding in adults (I2 = 48%, p = 0.65, OR = 0.87, 95% CI: 0.46–1.62), 30-day mortality (I2 = 0%, p = 0.61, OR = 0.83, 95% CI: 0.41–1.68), and ECMO duration in adults (I2 = 41%, p = 0.75, mean difference (MD) = −3.19, 95% CI: −23.01–16.63) and children (I2 = 76%, p = 0.65, MD = 40.33, 95% CI:−135.45–216.12). Conclusions: Compared with UFH, bivalirudin can be a safe and feasible alternative anticoagulant option to UFH as anticoagulation therapy in ECMO, especially for heparin resistance (HR) and heparin-induced thrombocytopenia (HIT) cases.